288 HEALTH CARE DELIVERY AND HOSPITAL-BASED CLINICAL OUTCOMES FOR NEONATES WITH CONGENITAL DIAPHRAGMATIC HERNIA IN CALIFORNIA USING THE AMERICAN ACADEMY OF PEDIATRICS NEONATAL INTENSIVE CARE UNIT CLASSIFICATION. (1st January 2006) - Evans, E.; Friedlich, P.; Kipke, M.; Seri, I.
Abstract : Objectives: To determine the pattern of health care delivery for patients with CDH and to assess the impact of the classification of neonatal intensive care units (NICUs) by the American Academy of Pediatrics (AAP) on clinical outcome for neonates with congenital diaphragmatic hernia (CDH). Methods: Data from the California Office of Statewide Health Planning and Development (OSHPD) were obtained for years 2001 to 2004. CDH patients were identified using ICD-9-CM code. NICUs were categorized using the AAP classification of (a) Level I (basic), (b) Level II (specialty), (c) Level IIIA (limited to conventional mechanical ventilation), (d) Level IIIB (high-frequency ventilation and iNO), (e) Level IIIC (major surgical repair center excluding cardiothoracic surgery ± ECMO), (f) Level IIID (major surgical repair center including cardiothoracic surgery ± ECMO). Frequency of the diagnosis of CDH per hospital and the probability for survival were calculated for each AAP NICU classification, patient cared for in the birth hospital (in-born) versus patients transferred to another institution for further care (out-born). For the purpose of data analysis, Level IIIC and IIID institutions were combined. Results: Of the 2, 087, 498 infants in the database, 500 patients were identified with CDH. The distribution of care for in-born CDH ( n = 429) was allocated to 16 Level I, 43 Level II, 25 Level IIIA, 55 Level IIIB, 33 Level IIIC, and 18 Level IIID NICUs. A significantly higher proportion of Level IIIC and D NICUs (41%) cared for more than 10 CDH patients as compared to lower complexity NICUs (Level I and II = 0%, Level IIIA = 4%, Level IIIB = 2%) [Chi 2 = 55; p = .0001]. Furthermore, 12% of Level IIIC and D NICUs cared for more than 15 CDH patients as compared to lower complexity NICU (Level I, II, and IIIA = 0%; Level IIIB =2% [Chi 2 =13; p = .02]. Level IIIC and D in-born CDH were 3.9 times more likely to die as compared to other in-born NICUs [95% OR CI = 1.4-11.6]. Out-born CDH infants in Level IIIC and D were 3.9 times more likely to die compared to neonates in lower level NICUs [OR 95% CI =1.4-11.5]. Conclusions: Our data indicate that (1) the proportion of level IIIC and D NICUs caring for more than 10 or 15 CDH neonates is significantly greater compared to other types of NICUs, (2) the relative risks for death in out-born and in-born Level IIIC and D NICUs are increased when compared to NICUs providing lower complexity of care.